2014
DOI: 10.1139/gen-2014-0108
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and association mapping of iron and zinc concentrations in chickpea (Cicer arietinumL.)

Abstract: Chickpea (Cicer arietinum L.) is the world's second most important pulse crop after common bean. Chickpea has historically been an important daily staple in the diet of millions of people, especially in the developing countries. Current chickpea breeding programs have mainly been directed toward high yield, biotic and abiotic stress resilience that has increased global production, but less attention has been directed toward improving micronutrient concentrations in seeds. In an effort to develop micronutrient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
116
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 54 publications
10
116
3
Order By: Relevance
“…Variation in grain Zn concentration among chickpea genotypes was previously reported (Khan et al, 2000;Kaya et al, 2009;Bueckert et al, 2011;Diapari et al, 2014;Ray et al, 2014). Responses to Zn applications were variable depending on the genotypes (Khan et al, 2000), which is not the case in our study.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Variation in grain Zn concentration among chickpea genotypes was previously reported (Khan et al, 2000;Kaya et al, 2009;Bueckert et al, 2011;Diapari et al, 2014;Ray et al, 2014). Responses to Zn applications were variable depending on the genotypes (Khan et al, 2000), which is not the case in our study.…”
Section: Discussionsupporting
confidence: 42%
“…Variations in Zn concentration and discrepancies in the extent of response to Zn application have been observed among chickpea genotypes (Khan et al, 2000;Bueckert et al, 2011;Diapari et al, 2014;Ray et al, 2014). For instance, Bueckert et al (2011) observed that in addition to differences in grain Zn concentration among individual genotypes, the kabulis have superior Zn concentration than the desi types.…”
Section: Introductionmentioning
confidence: 99%
“…Moisture stress occurred at vegetative and pod setting stage may have reduced zinc absorption and accumulation in the seeds, as shown across locations in 2012; while relatively sufficient moisture was available in 2013, resulting in higher grain yield, but dilution of grain zinc by grain carbohydrate increments. Previously, significant environment variation in grain zinc concentration was reported [4,28]. When the soil remains wet and becomes reduced, the availability of Mn, Fe, Cu, and P usually increases, and this condition is reversed under dry soil conditions [29].…”
Section: Discussionmentioning
confidence: 98%
“…The cultivar Arerti and the two breeding lines (FLIP07-27C and FLIP08-60C) had the highest seed zinc concentration compared to the rest of the cultivars and breeding lines. Several authors reported that there are significant variations in seed zinc concentration among chickpea cultivars [4,[23][24][25]. The variation in seed zinc concentration of the current chickpea cultivars and breeding lines could be due to variation in seed physiology, morphology, and tissue zinc distribution, which all are under genetic control [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation